Clinical characteristics of hospitalized male adolescents and young adults with avoidant/restrictive food intake disorder (ARFID) - Jason M. Nagata; Anita V. Chaphekar; Patrick Low; Ruben Vargas; Kyle T. Ganson; Anthony Nguyen; Sara M. Buckelew; Andrea K. Garber; Amanda E. Downey (Journal of Eating Disorders)
Abstract Background Avoidant/restrictive food intake disorder (ARFID) may result in significant medical sequelae. Compared to youth with eating disorders like anorexia nervosa (AN), youth with ARFID tend to be younger and are more likely to be male. We aim to describe sex differences in clinical characteristics of youth hospitalized for medical complications of ARFID and compare their characteristics with youth hospitalized for anorexia nervosa. Methods This is a retrospective review of electronic medical records for youth with ARFID (N = 36; 13 male and 23 female) and AN (N = 355; 40 male and 315 female), including restricting and binge-eating/purging subtypes, aged 9–25 admitted to the inpatient UCSF Eating Disorders Program (2012–2020). Results A greater proportion of youth with ARFID were male compared to youth with AN (36.1% vs. 11.2%). Male youth with ARFID (mean age 15.5 ± 2.8) had lower heart rate nadir (49.2 vs. 57.6 beats per minute, p = .019) and lower total cholesterol (129.8 vs. 159.3 mg/dL, p = .008), but higher hemoglobin (13.9 vs. 13.0 g/dL, p = .015) and prescribed calories at discharge (3323 vs. 2817 kcal, p = .001) compared to females with ARFID. Males with AN, who on average had higher admission BMI than males with ARFID (17.3 vs. 15.5 kg/m2, p = .013), required more (3785) kcal on discharge to restore medical stability than males with ARFID (3323 kcal). Compared to all youth with AN, youth with ARFID had lower body mass index (BMI, 15.7 vs. 17.0 kg/m2, p = .001) and lower vitamin D (26.5 vs. 33.0 ng/mL, p = .003). Conclusions ARFID in males is associated with lower heart rate nadirs than in females with ARFID. Clinicians should be aware of unique medical complications in youth with ARFID compared to youth with AN.